Etika dan Adab Murid kepada Guru dalam Kitab Taisirul Khalaq - Nasim, Siti; Utari, Dwi Desi Indah; Khairunnisa, Khairunnisa; Taufik, Nurut (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Students' ethics and manners towards teachers are the foundation of Islamic education which is now facing the challenges of modernization and digital culture. This study examines the values of students' manners in the book Taisirul Khalaq by Sheikh Hafidz Hasan al-Mas'udi and its relevance in the Syaichona Cholil Putri Islamic Boarding School in Balikpapan. Using descriptive qualitative methods through literature studies, observations, and interviews, it was found that the main values of manners include respect, politeness, sincerity, obedience, and simplicity. These values are implemented through role models and habits, where teachers become role models in showing polite, humble, and sincere attitudes, while students are accustomed to respecting teachers, obeying Islamic boarding school regulations, and maintaining simplicity in their daily behavior. And it remains relevant as a basis for forming the character of students who are knowledgeable and moral in the digital era